A comparative analysis of hysterectomy outcomes: robotic single-port vs. traditional transvaginal NOTES approaches - Yang, Qiannan; Lovell, Daniel Y.; Wu, Juliana; Zhang, Chunhua; Guan, Xiaoming (Frontiers in Medicine, 2025)
IntroductionThis study aimed to explore the feasibility and safety of robotic single port vaginal natural orifice transluminal endoscopic surgery (RSP-vNOTES) hysterectomy when compared with traditional vaginal natural orifice transluminal endoscopic surgery (T-vNOTES) hysterectomy.MethodsIn this study, the clinical data of 135 patients who underwent RSP-vNOTES or T-vNOTES hysterectomy performed by a single minimally invasive gynecologic surgeon from January 2017 to September 2024 were retrospectively analyzed. Clinical characteristics, surgical outcomes, perioperative complications, and postoperative pain scores were collected and analyzed.ResultsA total of 79 patients underwent T-vNOTES hysterectomy and 56 patients underwent RSP-vNOTES hysterectomy. Compared to the T-vNOTES group, the RSP-vNOTES group demonstrated a lower median body mass index (27 vs. 30 kg/m2, p = 0.04), fewer vaginal deliveries (0 vs. 1, p = 0.02), and a lower median uterine weight (90 vs. 175 g, p = 0.001). In terms of concomitant procedures, the RSP-vNOTES group more frequently underwent interventions related to endometriosis management—including excision of endometriotic lesions, lysis of adhesions, ovarian cystectomy, oophoropexy, bowel shaving, and bowel oversewing (all p < 0.05). A multiple linear regression analysis was performed to adjust for these differences. After adjustment, no significant differences were observed between the groups in hysterectomy time, total operative time, estimated blood loss, or postoperative pain scores. Conversion to laparoscopy or laparotomy occurred in six cases in the T-vNOTES group and in one case in the RSP-vNOTES group, although this difference did not reach statistical significance. Similarly, no significant differences were observed in intraoperative or postoperative complications between the groups.DiscussionWhen compared to T-vNOTES hysterectomy, RSP-vNOTES hysterectomy appears more feasible and safer for surgery, especially in cases involving concurrent endometriosis resection, and warrants further consideration as a skillset in a gynecologic surgeon’s toolbox. Large multicenter studies involving multiple surgeons and longer follow-up are needed to fully establish the safety and feasibility of this approach.